1994
DOI: 10.1007/bf00227454
|View full text |Cite
|
Sign up to set email alerts
|

Increasing sensitivity and specificity of Doppler sonographic detection of renal transplant rejection with serial investigation technique

Abstract: Acute rejection episodes are the most common cause leading to loss of renal grafts in the early postoperative phase. Doppler sonography presents a noninvasive tool to detect increased arterial blood flow resistance as a result of rejection. This can be measured by the increase in the resistive index (RI) and the pulsatility index (PI). In a prospective study including 65 consecutive patients we investigated whether the detection of rejection episodes is improved by determining RI or PI serially twice a week in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
1
10
1
4
Order By: Relevance
“…Ultrasound characteristics of rejection occur only late after rejection and are nonspecific [16]. The addition of serial measurements of resistance index by colour-coded duplex ultrasound increases the sensitivity, but specificity remains low [17,18]. The diagnostic value of renal scintigraphy, especially for prediction of acute rejection, is also limited [19].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound characteristics of rejection occur only late after rejection and are nonspecific [16]. The addition of serial measurements of resistance index by colour-coded duplex ultrasound increases the sensitivity, but specificity remains low [17,18]. The diagnostic value of renal scintigraphy, especially for prediction of acute rejection, is also limited [19].…”
Section: Discussionmentioning
confidence: 99%
“…To date, no reliable factor has been identified that predicts long-term allograft survival. Doppler sonography is a non-invasive tool for detecting increased arterial blood flow resistance as a result of acute and chronic rejection [55]. Recently, Radermacher et al [54] investigated in a cohort of 601 patients at least 3 months after transplantation whether the renal segmental arterial resistance index (described as a percentage reduction of the end-diastolic flow compared with the systolic flow) might be a predictor of renal allograft survival.…”
Section: Acute or Chronic Graft Rejectionmentioning
confidence: 99%
“…Auch die FKDS oder die Powerdoppler-(PD-)Sonographie können die Diagnose im Einzelfall nicht sicherstellen [22,23]. Eine engmaschige sonographische Verlaufskontrolle in der Frühphase nach NTX ist hingegen hilfreich, um sich gemeinsam mit Klinik und Paraklinik der Diagnose einer akuten Organabstoßung zu nähern und die Indikation zur Biopsie zu stellen [24]. Die Spezifität der FKDS zur Diagnosestellung der Rejektion wurde mit 25 [25] bis 90 % [26] ebenso wie die angegebene Sensitivität mit 35 [27] bis 94 % [28] sehr verschieden bewertet.…”
Section: Introductionunclassified
“…In der Praxis hat sich dabei die Bestimmung des nicht perfundierten subkapsulären SauTab. 3 Berechnungsgrundlagen des RI und PI[16,24,28] Abb. 4 Darstellung einer 22 mm großen echofreien zystischen Läsion nach Nierenbiopsie A. Im Breitbanddoppler (ADF) zeigt sich eine AVFistel B, welche sich ohne Therapie spontan zurückbildete.…”
unclassified